Delayed diagnosis of traumatic posterior hip dislocation in a 6-year-old girl with 6 years follow up: a case report - Kwesi Baidoo, Paa; Adegah, Boniface (International Surgery Journal, 2017)
Though uncommon, cases of traumatic hip dislocation have been reported in children worldwide. Averagely, it is recommended that the acceptable duration for reduction after such dislocations is about 6 hours. Even with that there is about 5% documented chance of developing avascular necrosis of the head of the femur. The incidence of avascular necrosis increases with delayed relocation of the femoral head. We report a case involving a 6-year-old girl with a 2-week delayed diagnosis of a left posterior hip dislocation that was reduced and followed up for 6 years.